2023
DOI: 10.3390/vaccines11020446
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Epitope Mapping of the Plasmodium falciparum Malaria Vaccine Candidate GMZ2.6c in a Naturally Exposed Population of the Brazilian Amazon

Abstract: The GMZ2.6c malaria vaccine candidate is a multi-stage P. falciparum chimeric protein that contains a fragment of the sexual-stage Pfs48/45-6C protein genetically fused to GMZ2, an asexual-stage vaccine construction consisting of the N-terminal region of the glutamate-rich protein (GLURP) and the C-terminal region of the merozoite surface protein-3 (MSP-3). Previous studies showed that GMZ2.6c is widely recognized by antibodies from Brazilian exposed individuals and that its components are immunogenic in natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Here, we predicted five B-cell linear epitopes in the SARS-CoV-2 N protein (N (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) , N (89-104) , N (185-197) , N (277-287) , and N (378-390) ) and confirmed their natural immunogenicity based on their recognition by samples from Brazilian COVID-19 convalescent donors. These data are in agreement with previous studies of our group in which we experimentally validated more than 80% of predicted epitopes from viruses [51,52], bacteria [53,54], and protozoa [55,56]. Moreover, our data corroborate previous studies that suggested similar regions as targets of antibodies [4,50,57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we predicted five B-cell linear epitopes in the SARS-CoV-2 N protein (N (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) , N (89-104) , N (185-197) , N (277-287) , and N (378-390) ) and confirmed their natural immunogenicity based on their recognition by samples from Brazilian COVID-19 convalescent donors. These data are in agreement with previous studies of our group in which we experimentally validated more than 80% of predicted epitopes from viruses [51,52], bacteria [53,54], and protozoa [55,56]. Moreover, our data corroborate previous studies that suggested similar regions as targets of antibodies [4,50,57,58].…”
Section: Discussionsupporting
confidence: 93%
“…In Malaria research, the B-Cell epitope mapping of the Plasmodium falciparum malaria vaccine candidate GMZ2.6c offers valuable insights into the development of immunity against this deadly disease. By identifying the key epitopes recognized by antibodies, researchers aim to bolster our understanding of protective immunity [6].…”
mentioning
confidence: 99%